The T120P or M172V mutation on rv2172c confers high level para-aminosalicylic acid resistance in Mycobacterium tuberculosis - Jin-Tian Xu; Ji-Fang Yu; Tao Cheng; Ao Feng; Ping Yang; Jing Gu; Hong-Jun Yu; Jiao-Yu Deng (Emerging Microbes and Infections, 2024)
Although para-aminosalicylic acid (PAS) has been used to treat tuberculosis for decades, mechanisms of resistance to this drug in Mycobacterium tuberculosis (M. tuberculosis) clinical isolates have not been thoroughly investigated. Previously, we found that decreased methylenetetrahydrofolate reductase (MTHFR) activity of Rv2172c led to increased sensitivity to antifolates in M. tuberculosis. In this study, we collected the genome-sequencing data of 173 PAS-resistant and 803 PAS-sensitive clinical isolates and analyzed rv2172c mutations in those 976 isolates. The results showed that two mutations (T120P and M172V) on rv2172c could be identified in a certain proportion (6.36%) of PAS-resistant isolates. The results of AlphaFold2 prediction indicated that the T120P or M172V mutation might affect the enzymatic activity of Rv2172c by influencing nicotinamide adenine dinucleotide (NADH) binding, and this was verified by subsequent biochemical analysis, demonstrating the role of residues Thr120 and Met172 on NADH binding and enzymatic activity of Rv2172c. In addition, the effect of rv2172c T120P or M172V mutation on methionine production and PAS resistance was determined in M. tuberculosis. The results showed that both T120P and M172V mutations caused increased intracellular methionine concentrations and high level PAS resistance. In summary, we discovered new molecular markers and also a novel mechanism of PAS resistance in M. tuberculosis clinical isolates and broadened the understanding of the NADH-dependent MTHFR catalytic mechanism of Rv2172c in M. tuberculosis, which will facilitate the molecular diagnosis of PAS resistance and also the development of new drugs targeting Rv2172c.